2018
DOI: 10.1017/s0373463318000632
|View full text |Cite
|
Sign up to set email alerts
|

Orbit Determination Using Pulsar Timing Data and Orientation Vector

Abstract: X-ray Pulsar Navigation (XPNAV) uses the Time Difference of Arrival (TDOA) of the pulsar signal between the spacecraft and Solar System Barycentre (SSB) to determine position. In this paper, a novel method to improve the performance of XPNAV via exploiting the pulsar position vector is proposed. First, the field of view of the collimator is utilised to find the pulsar orientation direction. Then, a searching strategy based on the modified Powell method under given coordinate frames is proposed. We also mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…On the principles of UKF, a augmented state unscented Kalman filter (ASUKF) is proposed by regarding the system bias as a slowly time-varying augmented state; the simulation confirms its effectiveness and reliability [9]. Furthermore, a novel approach of the modified strong tracking Kalman filter (STUKF) is designed, which had introduced a defined suboptimal fading factor based on the orthogonality principle of the innovation vectors in the framework of the UKF into the prediction covariance to adjust the Kalman gain matrix; the effectiveness of the STUKF is demonstrated in the simulation experiments [10]. Recently, a lot of novel algorithms have been developed quickly, an Adaptive Divided Difference Filter (ADDF) algorithm is introduced, which had optimized pulsar's position vector error by maximizing the incident flux density recorded by the X-ray detector; its simulation results had revealed that the navigation performance of ADDF can be improved by 70% compared with that of UKF and DDF [11].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…On the principles of UKF, a augmented state unscented Kalman filter (ASUKF) is proposed by regarding the system bias as a slowly time-varying augmented state; the simulation confirms its effectiveness and reliability [9]. Furthermore, a novel approach of the modified strong tracking Kalman filter (STUKF) is designed, which had introduced a defined suboptimal fading factor based on the orthogonality principle of the innovation vectors in the framework of the UKF into the prediction covariance to adjust the Kalman gain matrix; the effectiveness of the STUKF is demonstrated in the simulation experiments [10]. Recently, a lot of novel algorithms have been developed quickly, an Adaptive Divided Difference Filter (ADDF) algorithm is introduced, which had optimized pulsar's position vector error by maximizing the incident flux density recorded by the X-ray detector; its simulation results had revealed that the navigation performance of ADDF can be improved by 70% compared with that of UKF and DDF [11].…”
Section: Introductionmentioning
confidence: 79%
“…where α is the right ascension angle, ∆α i is the first-order differential of right ascension, ∆α i 2 is the second-order differential of right ascension, δ is the real declination angle, ∆δ i is the first-order differential of the real declination angle, and ∆δ i 2 is the second-order of differential of the real declination angle. Then, combining Equation (10), the state equation of MASEKF is subsequently obtained. It can be shown as follows.…”
Section: The State Equationmentioning
confidence: 99%
“…The StarNAV is an attractive autonomous navigation approach for spacecrafts as the observed targets are stars, which distribute widely on the celestial sphere, and it is easier to capture at different locations and observe with high accuracy than the near celestial body (such as Earth, Moon and planets) used for the traditional celestial navigation system (Zhao et al , 2017). Generally, the optical signal from stars is stronger than the signal from pulsars used for the X-ray pulsar-based navigation system (Wang et al , 2015; Zhang et al , 2019; Gui et al , 2019). The positioning accuracy of the StarNAV method would degrade as the distance between the spacecraft and the main celestial body increases.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a critical role for the success of space missions, especially in the case that the failure occurs in the communication system toward the ground stations [1][2][3][4][5] . Many autonomous navigation schemes have been proposed, such as satellite stellar refraction navigation [6,7] , autonomous navigation using visible planets [8][9][10] and X-ray pulsar-based navigation (XNAV) [11][12][13][14] . Among these existing methods, the bearings-only autonomous navigation has the potential to achieve high accuracy with current technology [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%